Performance Evaluation and Model Checking Join Forces. - BAIER, CHRISTEL; HAVERKORT, BOUDEWIJN R.; HERMANNS, HOLGER; KATOEN, JOOST-PIETER (Communications of the ACM, 2010)
The article presents a discussion of improvements in computing which can be obtained by combining performance evaluation methods with model checking techniques. The idea of jointly working on quantitative verification and performance is described as a useful way of combining complementary functions. An overview of the history of the mathematical concepts involved is presented, from the first half of the 20th century to the early 21st century. Rules of correctness proofs, queuing and temporal logic are discussed.